Assessing the impact of staff-reported perceptions of students’ helping-seeking and adjustment on academic performance of students: a case of selected tertiary institutions - Bisschoff, Christo; Ayeni, Adebanji Adejuwon William (Frontiers in Education, 2025)
University students often face both intellectual and emotional pressures that can affect how well they perform in their studies. To deal with these challenges, one useful approach is help-seeking, where students reach out for support when needed. In many cases, staff have observed that students turn to them for guidance after attempts to get assistance from peers were not effective. Help-seeking plays an important role in how students adjust to university life, influencing their academic, psychological, and social experiences. Previous studies show the link between help-seeking and adjustment, but there are still gaps, especially in research that looks at these issues over time and across different cultural contexts. This study therefore sets out to explore how help-seeking, adjustment, and workload interact and shape the academic performance of university students. The study used a survey research methodology to gather quantitative data and analyze correlations among factors. Conducted in South Africa, it targeted full-time academic and support staff from Regent Business School and MANCOSA. Questionnaires were distributed to the entire population, yielding 247 valid responses out of 250 (98.8%). Descriptive and inferential statistics were employed for the analysis, while Structural Equation Modelling (SEM) was used to assess the presented hypotheses. Affective Factors (attitude toward support) emerged as the strongest determinant of academic performance (β = 0.478, f2 = 0.237, p < 0.001), highlighting the crucial role of students’ emotional engagement and motivational orientation. This implies that students who perceive institutional and peer support positively are more likely to achieve better academic outcomes. The strong effect size reinforces the value of fostering supportive academic environments that build emotional confidence. These results suggest that students who are emotionally engaged and well-adjusted, as well as those who actively seek help, are more likely to undertake greater academic tasks and responsibilities.